ISESCO and The International Knowledge Order - Abdelilah Bouasria (International Institute of Islamic Thought, 2001)
This article is representative of the “culturalist” school of thought in political science. Using a paradigm coined by Foucault, numerous faces of power in the international knowledge order are explored. Starting from the assumption that the burden of “cultural gate-keeping’’ rests heavily upon UNESCO’s shoulder, it is analyzed whether ISESCO can count as a counter-power. Once the flaws of the comparative framework that posits ISESCO as a “second UNESCO’ are shown, an Islamic methodology is used in order to see whether this Islamic cultural institution represents Islam or simulates it. Such an inquiry requires a discursive analysis of two institutions that share a common cultural goal using either the framework of internationalism or that of the Ummah.